Intersecting Spheres: Civil and Family Law in the Evolving Islamic Legal Landscapes of Iran, Egypt, and Indonesia - Fakhlaei, Mohammad Taqi; Dorafshan, Sayyed Mohammad Hadi Ghabooli; Fathoni, Sulthon (Fakultas Syariah UINSI Samarinda, 2025)
This article examines the complex relationship between civil and family law in Iran, Egypt, and Indonesia. These three Muslim-majority nations, despite their unique legal systems shaped by varying integrations of Islamic jurisprudence and Western influences, all face the challenge of harmonizing modern legal frameworks with religious norms. The paper investigates this dynamic by analyzing how each country’s legal system defines and governs the family within its civil law framework. We delve into their respective court structures, the hierarchy of statutory laws, and the significant role of religious authorities. Our comparative analysis reveals how these societies balance tradition and modernity in their legal landscapes, offering insights into their shared struggles and distinct approaches to personal status and broader civil regulation. The findings highlight the critical tension between traditional religious norms and modern legal frameworks, with the core result that Iran employs a unified religious-legal approach in which family law is part of civil law, While early Iranian family law, like that of Egypt and Indonesia, was influenced by civil-law individualism and limited largely to alimony obligations, contemporary Iranian law—similar to developments in Egyptian and Indonesian family law—has shifted toward prioritizing the protection and collective interests of the family. At the same time, Egypt maintains a dual system with state-controlled religious courts and codified civil law. Indonesia, on the other hand, utilizes a decentralized system that grants significant autonomy to religious courts but subjects them to national legal oversight. Each nation has developed a unique, albeit often conflicted, strategy to manage this delicate balance.